2014
DOI: 10.2337/db13-0511
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1R Responsiveness Predicts Individual Gastric Bypass Efficacy on Glucose Tolerance in Rats

Abstract: Several bariatric operations are currently used to treat obesity and obesity-related comorbidities. These vary in efficacy, but most are more effective than current pharmaceutical treatments. Roux-en-Y gastric bypass (RYGB) produces substantial body weight (BW) loss and enhanced glucose tolerance, and is associated with increased secretion of the gut hormone glucagon-like peptide 1 (GLP-1). Given the success of GLP-1–based agents in lowering blood glucose levels and BW, we hypothesized that an individual sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Nonetheless, in line with our data, in that study the postsurgical GLP-1 response was not an independent predictor of glucose tolerance status. We also acknowledge data obtained in rodents suggesting that differences in the sensitivity to GLP-1 could be implicated in the effects of RYGB on glucose tolerance (13). Nonetheless, though limited by our cross-sectional design, the current association study supports the notion that GLP-1 secretion does not play a critical role in the outcome of T2DM after SG.…”
Section: Discussionsupporting
confidence: 66%
“…Nonetheless, in line with our data, in that study the postsurgical GLP-1 response was not an independent predictor of glucose tolerance status. We also acknowledge data obtained in rodents suggesting that differences in the sensitivity to GLP-1 could be implicated in the effects of RYGB on glucose tolerance (13). Nonetheless, though limited by our cross-sectional design, the current association study supports the notion that GLP-1 secretion does not play a critical role in the outcome of T2DM after SG.…”
Section: Discussionsupporting
confidence: 66%
“…7,12,43). Exogenous administration of GLP-1 or its stable analog exendin-4, as well as PYY(3-36), has been shown in numerous preclinical and clinical studies to suppress food intake and lower body weight (e.g., (2,4,5,9,15,19,24,27,40,57,59) or to suppress hepatic glucose production (52), in some of them by directly acting on the brain. The stable GLP-1 receptor agonist exendin-4 is widely used by Type 2 diabetic patients to stabilize glucose levels and reduce body weight (30,43).…”
mentioning
confidence: 99%
“…However, vertical sleeve gastrectomy equally improves body weight and glycemic control in GLP-1R knockout (ko) and wild-type mice, indicating that GLP-1 action is not required for the metabolic benefits induced by the surgery [6]. Nevertheless, a recent study in rats showed that the presurgical responsiveness to GLP-1-induced weight loss predicts the postsurgical efficacy on improvement of glycemic control [7]. Furthermore, GLP-1R agonism enhances the weight-lowering efficacy of adjustable gastric banding and suggests that GLP-1 therapy is a valuable adjunct to adjustable gastric banding to optimize the efficacy of this minimally invasive surgery [8].…”
mentioning
confidence: 99%